2021
DOI: 10.23887/ijssb.v5i2.34976
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Discipline, Work Environment, and Work Commitment on Job Satisfaction

Abstract: This study aims to test and analyze the influence of Discipline, Work Environment and Work Commitment on Job Satisfaction of Employees of PT Ria Multi Solusindo Terrain.  The research method is quantitative approach, type of research is descriptive and quantitative nature of the research is descriptive explanatory. Methods of data analysis is multiple linear regression analysis. Sample collection techniques, namely the census. The study sample was 66 employees. Discipline, Work Environment and Work Commitment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…It can be seen based on the results of data processing which explains that the t-statistics value is greater than the t-count, which is 6.835 ≥ 1.96 so that H1 is accepted. This research is in line with the results of Prayekti & Aji Pangestu (2022); Jaskyte et al (2020); Ong et al (2021) which revealed that the work environment has a significant influence on job satisfaction. The study used work environment and job satisfaction variables.…”
Section: Discussion the Effect Of Work Environment On Job Satisfactionsupporting
confidence: 90%
See 1 more Smart Citation
“…It can be seen based on the results of data processing which explains that the t-statistics value is greater than the t-count, which is 6.835 ≥ 1.96 so that H1 is accepted. This research is in line with the results of Prayekti & Aji Pangestu (2022); Jaskyte et al (2020); Ong et al (2021) which revealed that the work environment has a significant influence on job satisfaction. The study used work environment and job satisfaction variables.…”
Section: Discussion the Effect Of Work Environment On Job Satisfactionsupporting
confidence: 90%
“…Connected to this research at PT Dakwah Inti Media, the existing work environment has an influence on job satisfaction. This occurs due to things that affect job satisfaction such as the work atmosphere, work facilities provided, employee relations with superiors, and relationships between coworkers that are well established enough to be able to create a positive sense of job satisfaction felt by employees (Ong et al, 2021). This is considered beneficial for the company because it does not rule out the possibility that the achievement targets of the company will be quickly met (Fathonah & Utami, 2010).…”
Section: Discussion the Effect Of Work Environment On Job Satisfactionmentioning
confidence: 99%
“…A positive sign on t statistic indicates that the direction of influence is positive, where the higher the work discipline, the higher the job satisfaction. Such results can be understood that the employee who is accustomed to discipline in work will fulfill his job satisfaction because all the rules in the work he does voluntarily on the basis of his own consciousness [18], [19], [20]. Thus, Ha4 which states there is a significant influence of work discipline on job satisfaction is accepted.…”
Section: Hypothesis Testing Resultsmentioning
confidence: 99%
“…This proved that roughly 10-15% of employees frequently arrived late to work, with approximately 10% skipping responsibilities during working hours (Watung et al, 2021). Effectiveness and efficiency, authority and responsibility, discipline, and initiative were also other elements capable of affecting performance (Ong et al, 2021).…”
Section: Introductionmentioning
confidence: 92%